Penerapan Standart Akuntansi Keuangan Entitas Mikro kecil dan Menengah Dalam Penyusunan Laporan Keuangan U.D PALWA GROUP - Anita Puspa Dwi; Dewi Silvia (Journal of Accounting Taxing and Auditing (JATA), 2022)
Financial statements are a tool for analyzing financial performance that can provide information related to financial position and business performance. The purpose of this study is to help business owners who in this study are UD. Palwa Group in making financial reports based on SAK EMKM. The method used is qualitative method. The research was conducted to identify financial activities and prepare financial reports based on SAK EMKM. This research is a case study with the object of research is an SME that has not implemented the preparation of financial statements based on SAK EMKM. Data were collected by means of interviews and documentation. This study shows that UD. Palw Group compiling financial reports is still very simple and manual because the owner of UD. Palwa Group only records income and expenses to obtain profit information. Keywords: Financial Report, SAK EMKM